Budget impact analysis of apixaban to treat and prevent venous thromboembolism in Italy - Bellone, Marco; Di Virgilio, Roberto; Di Rienzo, Paolo (Farmeconomia. Health Economics and Therapeutic Pathways, 2016)
BACKGROUND: Venous thromboembolism (VTE), a collective term for deep vein thrombosis (DVT) and pulmonary embolism (PE), is a serious vascular condition associated to high economic and clinical burden. Apixaban, a Novel Oral Anticoagulant (NOAC) has shown non-inferiority efficacy versus the current standard of care (low molecular weight heparin [LMWH]/vitamin K antagonist [VKA]) in the acute treatment and prevention of VTE and a significant reduction in the risk of bleeding. AIM: Evaluate the economic impact of the use of apixaban for treatment and prevention of DVT and PE from the perspective of the Italian National Health System (NHS). METHODS: A budget impact model was adapted in order to compare clinical outcomes and economic consequences associated to apixaban vs. LMWH/VKA and others NOACs over a three-year time horizon in the Italian setting. In the analysis two scenario were compared: status quo scenario without apixaban and an alternative scenario with apixaban. Only direct healthcare costs have been considered. RESULTS: Assuming a population of patients receiving apixaban over the first 3 years equal to 20,957, the introduction of apixaban is associated to an incremental saving of € 821,748 in the first years, € 1,250,454 in the second year, and € 1,866,466 in the third year. The total net saving over the 3-year period is € 3,938,668, which is a 2.47% decrease from the total budget for the status quo scenario without apixaban. This saving is mainly due to reduced VTE events and bleeds by apixaban. Indeed apixaban is associated with less VTE events (both fatal and non-fatal), less major bleeding and less Clinical Relevant Non Major (CRNM) bleeding with a total of 52 fatal events avoided. CONCLUSIONS: The listing of apixaban for the treatment of VTE (both DVT and PE) and the prevention of recurrent VTE provides both significant clinical advantages, in terms of deaths and events avoided, and economical advantages, consisting in a reduction in the total expenditure on the Italian NHS.